Research progress in nursing of multiple myeloma with ostalgia (多发性骨髓瘤骨痛患者护理模式研究进展) - WANG Qiumei (王秋梅) (中西医结合护理)
This paper summarized the common types of nursing for patients with multiple myeloma with ostalgia, including care bundles, extended care, Traditional Chinese Medicine emotional care, mind-mapping based care, PRECEDE-PROCEED mode-based nursing. Application prospect, advantages and disadvantages of different type of nursing interventions were analyzed for providing basis of further research on nursing of multiple myeloma with ostalgia. (本研究总结多发性骨髓瘤骨痛患者临床常见护理模式, 包括集束化护理模式、延续性护理模式、中医情志护理模式、思维导图护理模式、格林护理模式, 并分析应用前景, 探讨利弊, 旨在为多发性骨髓瘤骨痛护理模式的深入研究及制定提供参考及借鉴。)